Science process skills and biology learning outcomes of high school students through the application of the guided inquiry learning model - Sinta , Alvia Dewi; Agustina , Putri (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2024)
Science process skills are important skills to develop when studying biology. Science process skills can positively contribute to students' biology learning outcomes. The right learning model can develop science process skills and student learning outcomes. This study aims to determine the effect of implementing the guided inquiry learning model on students' science process skills and biology learning outcomes. This quasi-experimental study was conducted at SMA Al-Islam 1 Surakarta. The research design used was a posttest-only control group design. The sample in this study consisted of 2 classes, namely one class as a control class and one class as an experimental class. Sampling was carried out using cluster random sampling. The research instruments were post-test questions and observation sheets. Learning outcome data were obtained from the posttest results, while science process skills data were obtained from observation results. Data analysis was carried out quantitatively using the Mann-Whitney U test. The results showed that the guided inquiry learning model affected students' science process skills and biology learning outcomes by being able to improve both aspects (sig<0.05). The study concludes that the inquiry learning model affects science process skills and learning outcomes. It is recommended in biology learning to use a guided inquiry learning model.